Longitudinal Coupling of Depression in Parent–Adolescent Dyads: Within- and Between-Dyads Effects Over Time. (November 2021) - Griffith, Julianne M.; Young, Jami F.; Hankin, Benjamin L.
In the present work, we evaluated reciprocal, within-dyads associations between parents' and adolescents' depressive symptoms across two independent samples ( N = 327 and N = 435 dyads; approximately 85% biological mothers) assessed every 3 months for 2 years (Study 1) to 3 years (Study 2). Results of random intercept cross-lagged panel models converged to support positive contemporaneous patterns of cofluctuation in parental and adolescent depression such that within-persons deviations in parental depression were associated with same-direction within-persons deviations in adolescent depression at the same time point. In contrast, within-persons fluctuations in parental depression did not prospectively predict within-persons fluctuations in adolescent depression, or vice versa, across the follow-up period. Results held across boys and girls, as well as dyads with and without a parental history of depressive disorder. Overall, findings advance knowledge by demonstrating that after accounting for between-persons/dyads variance, parental and adolescent depression demonstrate contemporaneous cofluctuations but do not demonstrate within-dyads reciprocity over time.